Imago Dei anthropology in Dostoevsky's The Brothers Karamazov - Ghini, Giuseppe (Church, Communication and Culture, 2017)
The first part of the article deals with Dostoevsky's poetics of imago Christi in The Brothers Karamazov, i.e. with the intrinsic comparison between the characters of the novel and that special hero of the same novel that is Christ himself. Indeed, the figure of Jesus Christ not only occurs many times in The Brothers Karamazov, but the different characters strive towards Christ, are built upon Christ's figura, in the sense Auerbach used this term in his book Mimesis. From this point of view, Dostoevsky's poetics of imago Christi fits exactly with the pattern prefiguration-fulfillment, which the Fathers of the Church and their Medieval followers developed and used very often. In the second part of the article, patristic texts from Dostoevsky's personal library, such as St. John Chrysostom's writings, are analyzed as a source of imago Dei poetics. In particular, both St. John Chrysostom's Letter to Monks and the chapter Elders (Chapter V of the Book I of the novel) focus on starchestvo, on human 'inner image' and on the spiritual enterprise - the so-called podvig - that every character of the novel, following Christ, has to fulfil.